2006
DOI: 10.1080/08037050600650191
|View full text |Cite
|
Sign up to set email alerts
|

Low‐density lipoprotein receptor‐related protein 5 variant Q89R is associated with hypertension in Japanese females

Abstract: We examined the influence of the Q89R variant in low-density lipoprotein receptor-related protein 5 on hypertension in a large Japanese cohort. We used multivariate logistic regression analysis to adjust for the effects of other factors known to influence hypertension such as age, body mass index, blood chemistry and lifestyle. Our cohort consisted of 1444 males and 1161 females selected from 3834 male and 2591 female workers in a single company. Hypertension was defined as systolic blood pressure 140 mmHg and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…In humans, polymorphisms in LRP5 exhibit genetic linkage with elevated LDL cholesterol levels, hypertension, increased body mass index, and obesity (32,(58)(59)(60). In our studies, mice lacking Lrp5 in osteoblasts and osteocytes exhibited an age-related increase in fat mass and reductions in both lean mass and bone mass.…”
Section: Discussionsupporting
confidence: 53%
“…In humans, polymorphisms in LRP5 exhibit genetic linkage with elevated LDL cholesterol levels, hypertension, increased body mass index, and obesity (32,(58)(59)(60). In our studies, mice lacking Lrp5 in osteoblasts and osteocytes exhibited an age-related increase in fat mass and reductions in both lean mass and bone mass.…”
Section: Discussionsupporting
confidence: 53%
“…This finding appears to represent another example in which key osteoblast developmental signals simultaneously alter metabolic machinery to fulfil the bioenergetic needs of differentiated osteoblast functions. The concept that Lrp5 might have a role in fuel metabolism is further supported by evidence linking polymorphisms in human LRP5 gene (A1330V, Q89R) with increased total and LDL cholesterol levels, hypertension, increased body mass index and obesity . Similarly, mice globally deficient in Lrp5 are glucose intolerant and exhibit increased plasma cholesterol levels when fed a high‐fat diet; this phenotype results from reduced clearance of chylomicron remnants from the circulation .…”
Section: Energy Substrate Utilization By Bone Cellsmentioning
confidence: 96%
“…13 Mice with targeted disruption of lrp5 have low bone mass and persistent embryonic eye vascularization. [17][18][19] Recently, Mani et al 20 found a mutation in the LRP5 homologue LRP6 in a family with autosomal dominant early onset coronary artery disease, metabolic syndrome and osteoporosis. 15 On normal diet, lrp5-deficient mice showed impaired glucose tolerance and glucose-induced insulin secretion.…”
Section: Introductionmentioning
confidence: 99%
“…15 In humans, LRP5 polymorphisms have been associated with obesity, 16 hypertension and hypercholesterolaemia. [17][18][19] Recently, Mani et al 20 found a mutation in the LRP5 homologue LRP6 in a family with autosomal dominant early onset coronary artery disease, metabolic syndrome and osteoporosis.…”
Section: Introductionmentioning
confidence: 99%